KARAKTERISASI KEKERASAN DAN KEKUATAN TARIK BAJA TAHAN KARAT SS304 DENGAN VARIASI ELEKTRODA LAS BUSUR LISTRIK - Wisnujati, Andika; Mudjijana, Mudjijana; Sutoyo, Sutoyo (Jurnal Rekayasa Mesin, 2025)
This study examines the hardness and tensile strength characterization of SS304 stainless steel welded using different electrode variations in the Shielded Metal Arc Welding (SMAW) process. The research focuses on three types of electrodes: NSN 308, NSN 309L, and NSN 312, to evaluate their influence on the mechanical properties of the weld metal. Hardness testing was conducted using the Vickers method with a 200-gf load, while tensile strength testing was performed to assess ultimate tensile strength (σu), yield strength (σy), and elongation (ε). The results indicate that the selection of electrodes significantly affects the hardness and tensile properties of the welded joints. NSN 312 exhibited the highest hardness values, particularly in the weld metal and filler areas, suggesting the formation of hard phases such as martensite or chromium-rich ferrite, making it suitable for wear-resistant applications. NSN 309L demonstrated moderate hardness, indicating a more balanced microstructure that provides good toughness and ductility. NSN 308 showed the lowest hardness values, which can be beneficial for applications requiring greater deformability. In the tensile test, NSN 309L achieved the highest ultimate tensile strength 47.77 Kg/mm² and elongation 45%, suggesting an optimal balance of strength and ductility. NSN 312 exhibited the highest yield strength 46 Kg/mm², indicating better resistance to plastic deformation. Meanwhile, NSN 308 had lower tensile properties compared to the other electrodes.  Overall, electrode selection should align with specific application requirements. NSN 312 is recommended for wear-resistant applications, NSN 309L for structures requiring both strength and ductility, and NSN 308 for applications with lower mechanical stress.